EFEKTIVITAS PROGRAM KELUARGA HARAPAN DALAM UPAYA PENGENTASAN KEMISKINAN DI NAGARI LAGAN HILIR PUNGGASAN KECAMATAN LINGGO SARI BAGANTI KABUPATEN PESISIR SELATAN - EKARDO, APANDO - (Pendidikan Sosiologi, 2014)
Poverty is a multidimensional problem that is characterized by low average quality of life of the population, education, health, child nutrition, and sources of drinking water. Various attempts have been made by the Indonesian government to alleviate poverty such as the Jaring Pengaman Sosial (JPS), Subsidi Langsung Tunai (SLT), Beras Miskin (Raskin), Asuransi Kesehatan untuk Masyarakat Miskin (Askeskin), Bantuan Operasional Sekolah (BOS), Program Nasional Pemberdayaan Masyarakat Mandiri (PNPM), as well as the program was last launched the Family Hope Program (PKH). Efforts to tackle poverty is still considered not running as expected. So that the formulation of the problem in this research is: How can the effectiveness of the Family Hope Program (PKH) in poverty reduction efforts in Nagari Lagan Hilir Punggasan. The objectives of this study is to describe the effectiveness of the Family Hope Program (PKH) for poor households.The theory used in this study is the culture of poverty theory propounded by Oscar Lewis. This study used a qualitative approach with descriptive type. Determination of informants conducted by purposive sampling. Number inporman in this study of 17 people. Data was collected through observation, interviews, and document study. Then the unit of analysis is a group. Data analysis method used is descriptive analysis of the data was analyzed according to the model of interactive analysis of Milles and Heberman.From the research it can be concluded that the Family Hope Program in Nagari Lagan Hilir Punggasan been effective when seen from the program objectives, the goal of the program is increase the level of education of children households and increase access to education and health for children households. On the other hand targeting CCT beneficiaries for households in Nagari Lagan Hilir Punggasan can not be said to be effective. This is due to the targeting of CCT in Nagari Lagan Hilir Punggasan still not on target, because the field is still found in people who are categorized into the middle to upper economic assistance, targeting not only look at the economic conditions that are not capable, but given the relationship between cadres record with the local community.